X-ray dosimetry in breast cancer screening: 2D and 3D mammography. Issue 151 (June 2022) - Di Maria, S.; Vedantham, S.; Vaz, P.
Abstract: According to the World Health Organization (WHO), at the end of 2020, 7.8 million women alive were diagnosed with breast cancer in the past 5 years, making it the world's most prevalent cancer. It is largely recognized and demonstrated that early detection represents the first strategy to follow in the fight against cancer. The effectiveness of mammography screening for early breast cancer detection has been proven in several surveys and studies over the last three decades. The estimation of the Mean Glandular Dose (MGD) is important to understand the radiation-associated risk from breast x-ray imaging exams. It continues to be the subject of numerous studies and debates, since its accuracy is directly related to risk estimation and for optimizing breast cancer screening programs. This manuscript reviews the main dosimetry formalisms used to estimate the MGD in mammography and to understand the continuing efforts to reduce the absorbed dose over the last forty years. The dosimetry protocols were formulated initially for mammography. Digital breast tomosynthesis (DBT) either in conjunction with synthesized digital mammogram (SDM) or with digital mammography (DM), is routinely used in many breast cancer screening programs and consequently the dosimetry protocols were extended for these techniques.